Measuring people's trust - John Ermisch; Diego Gambetta; Heather Laurie; Thomas Siedler; S.C. Noah Uhrig (University of Essex, Institute for Social and Economic Research (ISER), 2008)
We measure trust and trustworthiness in British society with an experiment using real monetary rewards and a sample of the British population. The study also asks the most typical survey question that aims to measure trust, showing that it does not predict trust as measured in the experiment. Overall, about 40% of people were willing to trust a stranger in our experiment, and their trust was rewarded one-half of the time. Analysis of variation in the trust behaviour in our survey suggests that trust is more likely if people are older, their financial situation is comfortable, they are a homeowner, or they are divorced or separated. Trustworthiness is less likely if a persons financial situation is perceived by them as just getting by or difficult.
Keywords: 330